Simulasi Integrasi Leach dan Enkripsi untuk Efisiensi Jaringan Sensor Nirkabel - Gede Dimas Putra Pratama; I Gede Arta Wibawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
The development of Wireless Sensor Network (WSN) has a significant impact on various fields such as smart agriculture, environmental monitoring, and IoT-based security systems. The main drawbacks of WSN are the limited energy, computing capacity, and transmission power of sensor nodes. The Low-Energy Adaptive Clustering Hierarchy (LEACH) protocol is widely used for energy management by forming clusters and reducing long-distance transmission. However, LEACH does not yet have a built-in security mechanism, making it vulnerable to threats such as eavesdropping and data manipulation. This study proposes the integration of the lightweight encryption algorithm XOR Cipher into the LEACH protocol to improve data security without reducing energy efficiency. Software-based simulations using Python were conducted to compare the performance of standard LEACH and encrypted LEACH. The parameters tested include energy consumption, packet delivery ratio (PDR), delay, and packet loss. The results show that the integration of XOR Cipher adds very little overhead, with slightly increased energy consumption and delay, but the PDR remains above 90%. This proves that XOR Cipher is a lightweight encryption solution that is feasible to be applied to WSN.